Diagnosis, risk factors, and treatment of pediatric benign pneumoperitoneum: A single‐center retrospective study - Yueyue Liu; Quan Kang; Guobin Liu (Pediatric Discovery)
Abstract Pneumoperitoneum is one of the common acute abdominal emergencies that leads to surgical exploration in children, but not all pneumoperitoneum require emergency surgery. This study evaluated the diagnostic methods, predisposing risk factors, and therapeutic options in children with benign pneumoperitoneum for accurate diagnosis and reducing the risk of adverse surgical consequences. A total of 63 cases of pneumoperitoneum diagnosed by the radiographs were involved in this study and were divided into the surgical pneumoperitoneum and benign pneumoperitoneum groups, respectively, from 2009 to 2021. The general information, abdominal signs, laboratory examination, therapies and outcomes, total hospitalization time, and comorbidities were analyzed. Logistic regression analysis assessed the risk factors and protective factors of benign pneumoperitoneum. Promising biomarkers underwent receiver operating characteristic curve analysis. Children with surgical pneumoperitoneum were younger than those with nonsurgical pneumoperitoneum in the study. The C‐reactive protein (CRP) level in the surgical pneumoperitoneum group was higher than that in the other group, albumin (ALB) was lower than that in the benign pneumoperitoneum group, and the ratio of ALB to CRP can be used as an effective indicator to predict whether the pneumoperitoneum is benign or whether surgery is needed. Pulmonary injury, pneumonia, and blunt abdominal injury are the major causes in patients with benign pneumoperitoneum. The establishment and management of clinical criteria for the diagnosis of benign pneumoperitoneum in children will be important for the treatment and recovery of children diagnosed with pneumoperitoneum.